"Chisel marks" on columnar joint face - Wojtal, Steven F. (Oberlin College Library, 1997)
The sides of any columns in columnar jointing do not form a single uniform fracture, rather they grow incrementally. Each subhorizontal fracture increment, known as a "chisel mark," has its own fracture surface markings that indicate the direction of growth of that fracture. Most fractures here propagated from left to right across the column face, and most of these fractures initiated along the lower edge of the chisel mark.